Leptospirosis in the Republic of Tatarstan. Epidemiological Features - T. A. Savitskaya; V. A. Trifonov; I. V. Milova; G. Sh. Isaeva; I. D. Reshetnikova; I. V. Serovа (Проблемы особо опасных инфекций, 2021)
The study presents a characteristic of the current epidemiological situation on leptospirosis in the Republic of Tatarstan, investigation of the circulation of leptospirosis agents among the population of small mammals, and the species composition of Leptospira that caused diseases in humans.Materials and methods. The paper contains the data on the incidence of leptospirosis among the population in the Russian Federation (RF) for the period between 2000 and 2018, in the Republic of Tatarstan – since 1998, submitted by the Rospotrebnadzor Administrations in the constituent entities of the Russian Federation, materials of the Center for Hygiene and Epidemiology in the Republic of Tatarstan and the Main Veterinary Administration of the Republic of Tatarstan.Results and discussion. We have carried out the analysis of the epidemiological situation in the Republic of Tatarstan for the period of 1998–2018, by the administrative territories of the republic. The incidence of human leptospirosis caused by various leptospira serogroups has been assessed. In total, 112 people got infected with leptospirosis during the analyzed period. Also the data of epizootiological survey of small mammals inhabiting the natural foci of leptospirosis in the republic are presented. Laboratory tests of 1565 samples from mouse-like rodents for the presence of leptospirosis pathogens have been performed. 1.9 % of the tests gave a positive result. Dominant in the Republic of Tatarstan are the serogroups of Leptospira – Leptospira grippotyphosa and L. hebdomadis. The results of laboratory studies on the carriage of leptospira among small mammals and contamination of environmental objects indicate the circulation of pathogens of leptospirosis in the population of small mammals, habitant in forest shrub, near-water and meadow field stations of the republic. The red vole prevails in this community, the average index of its dominance is 66.7 %. Epizootiological monitoring point to a latent epizootic process in the community of mouse-like rodents.